MEDICAL AND ENVIRONMENTAL ESTIMATION OF THE ENVIRONMENT OF BOTLIKH AND NOVOLAK DISTRICTS OF DAGESTAN - G. M. Abdurakhmanov; M. G. Daudova; A. G. Gasangadzhieva; E. G. Abdurakhmanova; P. I. Gabibova (Юг России: экология, развитие, 2014)
The state of water quality, soil and pasture vegetation areas Novolaksky Botlikh and the Republic of Dagestan in order to identify those areas kokantserogennyh carcinogenic and environmental factors.